Teoria Critica francofortese (1922-1933) - Mario Gennari (Studi sulla Formazione, 2025)
The article examines the Frankfurt School (firstly investigating its Jewish-German origin) and the Kritische Theorie elaborated therein: a theory of society that uses Hegel, Marx, and, in part, Freud to develop a radical critique of bourgeois society, capitalist ideology, National Socialism, and the culture industry. Of this School — here considered as the most unusual and original among the schools of thought in early twentieth-century German philosophy — the essay investigates the period ranging from its foundation to the escape of its members from Hitlerian Germany.